Integrating ESG (Environmental, Social, Governance) into Strategic Planning for Islamic Banks: Implications for Performance and Competitiveness - Prilaksono, Kursusantyo Dudung; Novianty, Ira (Integrasi Sains Media, 2025)
Phenomenon. The growing global emphasis on Environmental, Social, and Governance (ESG) has reshaped sustainable finance practices. However, Islamic banks face distinct challenges in integrating ESG due to the need to align it with Shari’ah compliance, which emphasizes justice, ethical conduct, and long-term sustainability. The conceptual divergence between conventional ESG frameworks and Islamic values raises uncertainty regarding the strategic internalization of ESG in Islamic banking. Purpose. This study synthesizes the literature published between 2015 and 2024 to examine how ESG is integrated into the strategic planning of Islamic banks and its implications for sustainable performance and competitiveness, considering the mediating role of strategic processes and the moderating role of Shari’ah governance. Research Gap. Prior studies largely treat ESG as a stand-alone reporting practice rather than a strategic driver, while integrated analyses linking ESG, strategic planning, and Shari’ah governance remain scarce. Findings. Based on a PRISMA-guided Systematic Literature Review, the findings reveal that ESG adoption in Islamic banks remains predominantly symbolic due to fragmented standards and limited strategic embedding. ESG contributes meaningfully to sustainable performance and competitiveness only when embedded in strategic processes and reinforced by effective Shari’ah governance. Implications and Novelty. This study positions ESG as a value-based strategic mechanism and provides the first integrative review linking ESG, strategic planning, and Shari’ah governance within a unified conceptual framework to explain sustainable performance and competitiveness in Islamic banking.